Play model for "evaluation of self-concept of children with cancer" - Gulay Manav; Ayse Ferda Ocakci (Wolters Kluwer Medknow Publications, 2016)
Background: Childhood cancers are fatal diseases which cause intense stress and traumatic situations for the ones who experience those diseases. This kind of an emotionally hard life may create some hardships for developing self-concept. The aim of the study is to put forth the self-exposure of a school-age child by using plays. Materials and Methods: Six play sessions had been carried out in June-August 2011. As a searching pattern, interpretive case study method was used. The research consisted of six children with cancer, aged between 9 and 12 years. The research was conducted in a public hospital in children oncology service. Results: The assessment of data was realized in two stages. The first one was examining the data; the other stage was the content analysis that has been constructed after the play sessions as "Nursing Intervention: Play Model." In the newly formed model, nine themes had been found: (a) expressing good memories, (b) control, (c) problem-solving ability, (d) relations, (e) aggressive behaviors, (f) regression, (g) good-bad, (h) trauma, and (i) anxiety. Conclusions: The self-concept of the school-age child needs to be supported. It has been submitted that the themes can be supportive for the prospective nursing models concerning child's self-exposure. It has been suggested that the themes produced by "Nursing Intervention: Play Model" can be used while planning, implementation, and assessment of the nursing care.